2011
DOI: 10.1016/j.jmaa.2011.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Uniform estimates for the finite-time ruin probability in the dependent renewal risk model

Abstract: This paper investigates the finite-time ruin probability in the dependent renewal risk model, where the claim sizes are independent and identically distributed random variables with strongly subexponential tails, and the interarrival times are negatively dependent. We establish an asymptotic estimate, which holds uniformly for the time horizon varying in the positive half line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…As (2) and (3), define the infinite-time and finite-time ruin probabilities of risk model ( 19) with (⋅) replaced by * (⋅), denoting them by * ( , ) and * ( ), respectively. The following first lemma comes from Corollary of Wang et al [9]; see some similar results in Yang et al [8].…”
Section: Proofs Of Main Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…As (2) and (3), define the infinite-time and finite-time ruin probabilities of risk model ( 19) with (⋅) replaced by * (⋅), denoting them by * ( , ) and * ( ), respectively. The following first lemma comes from Corollary of Wang et al [9]; see some similar results in Yang et al [8].…”
Section: Proofs Of Main Resultsmentioning
confidence: 71%
“…In the past decade, more and 2 Complexity more attention has been paid to heavy-tailed claims and the dependence between them. In the presence of heavy-tailed claim sizes, Tang [5], Leipus andŠiaulys [6,7], Yang et al [8], Wang et al [9], Liu et al [10], Yang and Yuen [11], Yang et al [12,13], and Chen et al [14] investigated some independent or dependent risk models with no by-claims. Li [15] considered a dependent by-claim risk model with positive interest rate and extendedly varying tailed main claims and by-claims under the pairwise quasi-asymptotical independence structure (see the definition below).…”
Section: Introductionmentioning
confidence: 99%
“…The properties of class S * and related classes were studied in [6,Sect. 3.4], [8][9][10][11][12][13][14], [18][19][20], and other papers. In particular, it is well known that, under µ F < ∞, it holds that S * ⊂ S ⊂ L .…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…showing the validity of (19). It remains to prove inequality (20). Integral from this inequality is bounded from below by J F ,G (x) :=…”
Section: Proof Of the Theoremmentioning
confidence: 97%
“…Leipus and Šiaulys [3] and Kočetova et al [4] considered the claim sizes have strong subexponential distributions and showed the asymptotics of ψ(xt) holds uniformly for t Î[ f (x)¥). Yang et al [5] and Wang et al [6] improved the above results by considering the dependent {θ i i ≥ 1}.…”
Section: Introductionmentioning
confidence: 96%